Pulse power supply of diode-pumped solid-state lasers - Дзюбенко, М.И.; Коленов, И.В.; Пелипенко, В.П.; Дахов, Н.Ф. (Radiotekhnika, 2020)
Recently, solid-state pumped semiconductor lasers have become increasingly widespread. Lasers of this type have several advantages over solid-state lasers with lamp pumping. First of all, this is high efficiency, long service life, small dimensions and weight. The use of semiconductor laser diodes for pumping solid-state active media imposes a number of rather stringent requirements on the power sources of laser diodes. The power source should provide rectangular current pulses with a flat top, a steep leading edge of the pulses and the absence of reverse current surges at the trailing edge. A pulsed power source for a diode pump system of a ytterbium-erbium laser was developed, manufactured and studied. In this source, the control unit provides functions for protecting the load in emergency conditions, controlling the charge of the storage capacitors to the required voltage and generating current pulses to power the laser diode line. The current is regulated by a field effect transistor operating in a linear mode. The load is included in the source circuit of the field-effect transistor, and the reference signal is generated by the DAC of the microcontroller. Such an approach made it possible to create a relatively simple, reliable and small-sized laser power source with a wide range of adjustment of the duration and amplitude of current pulses. This makes it possible to select the optimal operating mode depending on the characteristics of the active medium of the laser. Particular attention is paid to solving the problems of protecting expensive rulers of laser diodes from failure. The developed source can be used to pump other solid-state lasers with shorter lifetimes of the upper laser level than erbium.